-2(1-a)+5=6-(a-1)

Simple and best practice solution for -2(1-a)+5=6-(a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1-a)+5=6-(a-1) equation:


Simplifying
-2(1 + -1a) + 5 = 6 + -1(a + -1)
(1 * -2 + -1a * -2) + 5 = 6 + -1(a + -1)
(-2 + 2a) + 5 = 6 + -1(a + -1)

Reorder the terms:
-2 + 5 + 2a = 6 + -1(a + -1)

Combine like terms: -2 + 5 = 3
3 + 2a = 6 + -1(a + -1)

Reorder the terms:
3 + 2a = 6 + -1(-1 + a)
3 + 2a = 6 + (-1 * -1 + a * -1)
3 + 2a = 6 + (1 + -1a)

Combine like terms: 6 + 1 = 7
3 + 2a = 7 + -1a

Solving
3 + 2a = 7 + -1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'a' to each side of the equation.
3 + 2a + a = 7 + -1a + a

Combine like terms: 2a + a = 3a
3 + 3a = 7 + -1a + a

Combine like terms: -1a + a = 0
3 + 3a = 7 + 0
3 + 3a = 7

Add '-3' to each side of the equation.
3 + -3 + 3a = 7 + -3

Combine like terms: 3 + -3 = 0
0 + 3a = 7 + -3
3a = 7 + -3

Combine like terms: 7 + -3 = 4
3a = 4

Divide each side by '3'.
a = 1.333333333

Simplifying
a = 1.333333333

See similar equations:

| 5x+7(3x-18)=4 | | -93=-7n+5 | | 4(3a-1)=10-(a+3) | | -24+h=-45 | | 3(x-4)-8=2x | | 3(1-2y)=8-3y | | 5+6y=y+20 | | 5(2a+7)=5(4-a) | | 5(x-2)=3x-12 | | 1=x+1/16 | | -12-66=-9x+21 | | 4a+6=2a+20 | | 10(x-3)=5(x+5) | | 41+6=2a+20 | | 3x-(6+2x)=22 | | -83=4r-7 | | 5(y+4)=3y+6 | | 1.16y-6=8 | | -5x-22=38-2x | | x+6x-3-2x=27 | | 1+n=-3 | | -4(a+6)+14=10 | | 2(5y+3)=46 | | 3x-45=24+6x | | -72=18x | | 36x^2+9y^2=81 | | -12x-82=74-6x | | -30=v-10 | | 51=-3a | | -7x-162=9x+46 | | 5(m+3)=2(3m+1) | | (94)=136 |

Equations solver categories